Eksplorasi Perilaku Investor Individu Dalam Pengambilan Keputusan Investasi Suatu Pendekatan Fenomenologi - Yudi Akhmad Sadeli; Amiruddin Amiruddin; Darmawati Darmawati (AkMen JURNAL ILMIAH, 2021)
This study aims to see how individual investors' behavior is determining their investment decisions. Investor behavior has a vital role in making investment decisions in the capital market because an appropriate investment decision is based not only on mere fundamental factors as rational aspects but also by psychological factors, namely investor behavior, which is an irrational aspect in stock trading. This research is qualitative research with a phenomenological approach using an interpretive paradigm. The phenomenological method used is the phenomenology of Schutz, a phenomenological method used to interpret the behavior of investors based on their motives. Judging from the investor personality group, the order of investor personality group consists of Individualist, Adventurer, and Guardian, while the Celebrity behavior group has not been found. Good knowledge about investment and emotional control and learning from experience are factors that determine investor behavior in stock transactions. Understanding investment and trading mechanisms and continuing to learn from any source is a permanent primary capital that investors need to have and continue observing and responding to developing economic issues.